Twisted Religious Politics and Oppression of Women in Khaled Hosseini’s A Thousand Splendid Suns - Kareem, Hasanain Ali; Amjad, Fazel Asadi (International Journal of Psychosocial Rehabilitation, 2020)
This paper is the study of the aspects that lead to the decadence of the public life of the Afghan women and the restriction of freedoms caused by extremist religious politics. Afghanistan is considered a conservative country that adheres to strict cultural norms and regulations. One such system is the hardline religious system, which has grown tougher after the Taliban seized power. Persecution of women and restricting their freedom due to narrow religious thought and extremist religious policies are among the most important topics discussed in Husseini’s novels. Adorno’s theory "The Authoritarian Personality" was taken primarily to analyze the religious aspect of the addressed novel. The study has focused on the activities and practices of these groups which take religion as a source of authority. That authority has contributed to doubling the oppression of women. The study has adopted the socio-religious framework to illustrate the policies which persecuted women by using strict religious rulings.